2017
DOI: 10.1371/journal.pone.0184076
|View full text |Cite
|
Sign up to set email alerts
|

Associations between endothelial dysfunction and clinical and laboratory parameters in children and adolescents with sickle cell anemia

Abstract: BackgroundHematological changes can drive damage of endothelial cells, which potentially lead to an early endothelial dysfunction in patients with sickle cell anemia (SCA). An association may exist between endothelial dysfunction and several clinical manifestations of SCA. The present study aims to evaluate the links between changes in endothelial function and clinical and laboratory parameters in children and adolescents with SCA.MethodsThis study included 40 children and adolescents with stable SCA as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Other studies demonstrated an abnormal response in FMD after wall shear stress (WSS) for transient arterial occlusion in SCA adults [17,37] and children [38]. Studies by our research group showed similar results with decreased FMD in SCA [21,26].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Other studies demonstrated an abnormal response in FMD after wall shear stress (WSS) for transient arterial occlusion in SCA adults [17,37] and children [38]. Studies by our research group showed similar results with decreased FMD in SCA [21,26].…”
Section: Discussionsupporting
confidence: 77%
“…Endothelial function was evaluated using a protocol established under the guideline for the ultrasonographic evaluation of FMD with reactive hyperemia of the brachial artery [23][24][25] and already used in previous studies carried out by our research group [21,26]. Briefly, the moving images were scanned, beginning 30 seconds before the cuff was deflated until 2 minutes later, allowing for subsequent analysis.…”
Section: Technical Informationmentioning
confidence: 99%
“…This study was comprised of secondary analyses of data collected and expanded on previously completed research (7), which included children and adolescents aged between 6 and 18 years, diagnosed with SCA, with or without the use of hydroxyurea and age-matched healthy children. The participants were assigned to two reference centers for the treatment of hematological diseases, including the Hematology Outpatient Clinic of the Magalhães Neto Ambulatory-HUPES Complex of the Federal University of Bahia Medical School, and Hematology and Hemotherapy Foundation of Bahia (HEMOBA).…”
Section: Methodsmentioning
confidence: 99%
“…Low oxygen levels further cause increased red cell deformation and polymerization which also cause damage to vascular endothelial cells (Sedrak and Kondamudi, 2018). Vascular endothelial cells dysfunction results in altered vascular tone, vascular adhesion and receptor function related with inflammatory responses and oxidative damage were observed in SCD patients (Teixeira et al, 2017). Oxidative stress during SCD has also been reported to cause depletion of cellular antioxidants resulting in increased lipid peroxidation and increased fragility of RBCs (Okorie et al, 2018).…”
Section: Introductionmentioning
confidence: 99%